Trema u kaznodziejów. Specyfika i sposoby opanowania - Kalbarczyk, Adam (Studia Pastoralne, 2026)
Phenomenon of a stage freight – no matter how we define it – is a common problem also experienced by preachers. Specific features of preachers’ stage freight is related to its theological connotations. Its source, most of all, is an awareness of the duty to preach the Gospel and priestly responsibility for the Word of God mixed with anxiety of being unworthy of the mission bestowed upon them and an ordinary human fear of failure and embarrassment. Since the sources of preachers’ stage freight are of a theological character, it is also mainly a supernatural level on which it should be dealt with - through prayer, development of a preacher’s spiritual life, openness to the Holy Spirit as well as a constant care of a proper, preliminary and final, preparation for preaching. When it comes to an anthropological dimension it is important for a preacher to develop an internal balance between an emotional tension and a thoughtful assessment of one’s abilities – through affecting a psychic and somatic sphere by an autosuggestion and relaxation techniques. Nevertheless a preacher should remember that a moderate stage freight is almost a necessary phenomenon, since an optimal level of a psychic tension (for a specific person) is good for one’s readiness. After all, what kind of a preacher it would be, if he lacked passion and involvement while preaching!